Learning Analytics: The Relationship between Cultural Differences and Online Behaviors - Pholmat, Patiphan; Silpasuwanchai, Chaklam (Journal of Education Studies, Chulalongkorn University, 2019)
This paper investigated online behaviors from 233 students using the Blackboard platform. Descriptive and inferential statistics were performed, crossing cultures and online behaviors with a focus on Learning Analytics method. Culture was found to have a significant effect on online behaviors, in which there is significant difference between cultures on content view counts (p = .015). There is no significant effect of cultures was found on assignment submission counts (p = .22) or discussion submission counts (p = .084). Further post-hoc analysis with Bonferroni correction confirms the difference between Africa and Europe and America, between South Asia and Europe and America, and between East Asia and Europe and America (all p < .01). However, one interesting finding shows that Asian students tend to be more involved in the learning management system as compared to their Western counterparts.